Exploring the Arctic deep-sea by color filters - Os, Vibeke; Zimmermann, Heike Jane; Panieri, Giuliana (Septentrio Educational, 2023)
Focus: To get to know some of the creatures in the deep-sea that use color and the lack of light to camouflage themselves. Learning objectives: With these TWO activities, we use vision to explore life forms in the deep sea which have adapted to extreme conditions. Through the activities, the pupils will also become familiar with some organisms well-hidden at the bottom of the ocean. Key words: Camouflage strategies, Deep sea ocean, Physical effects of light, Characteristics of sea lifeforms